CURRENT STATE AND DIRECTIONS FOR ACTIVATION OF BANK LENDING IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Voloshchuk V.R., Katsan A.M. CURRENT STATE AND DIRECTIONS FOR ACTIVATION OF BANK LENDING IN UKRAINEPurpose. The aim of the article is the identification of trends, problems and directions of activation of bank lending as one of the main factors in ensuring the development of a bank's credit strategy and sustainable development of the real economy.Methodology of research. The dialectical method of scientific knowledge, systemic and logical approaches is used to accomplish research tasks and achieve the set goal. The following general scientific methods have been applied in the process of research: economic and statistical – to generalize the trends of bank lending in Ukraine; tabular – for a clear display of the results of the study of volumes of lending, broken down by type of currency and maturity; abstract and logical – in the formation of conclusions and proposals.Findings. The tendencies of bank lending in Ukraine are determined and summarized. The main ways of improving the availability of lending are systematized. Possible directions of activation of bank lending and realization of the bank's credit strategy are outlined. It has been established that effective economic development is possible only with the active development of the real sector of the economy, which should be the priority object of bank lending.It is substantiated that loans granted to enterprises of the real sector will contribute to the development of production, especially if they are aimed at modernization, technical re-equipment and innovations. It has been determined that the activation of lending for acceptable interest rates and long terms of loans for business entities requires a comprehensive settlement, in particular, measures to this should be related to the need to support the real sector of the economy by the state and to encourage banks to provide loans.It is envisaged that the growth of banks' lending activity and the diversification of types of lending activities should be predictable, provided with the development of a clearly formulated credit strategy consistent with the corporate.Originality. Further development of analytical tools for identifying trends in bank lending and the ability of the banking system to meet the needs of business entities with the necessary cash resources for further growth of the domestic economy, as well as mechanisms for increasing the affordability of bank lending, have been further developed; further study of the formalization of the impact of bank lending on the development of the economy and the banking system; definition of the directions of activation of bank lending for the implementation of the state strategy in the banking sector, which is based on the goals of economic growth.Practical value. The obtained results of the research can be used by banks, enterprises and business and the population to restore lending processes at acceptable interest rates. A comprehensive settlement is needed in order to ensure effective lending, in particular, support is needed for the real sector of the economy from the state, and stimulate banks to provide loans; expansion of the range of credit products, introduction of new customer service technologies, development of new markets for banking services, state support and development of a bank's credit strategy.Key words: state; lending; clients; services; products; strategy; provision; banks; rates; needs; economy.
Keywords: Key words; state; lending; clients; services; products; strategy; provision; banks; rates; needs; economy.